Number and Location of Positive Nodes, Postoperative Radiotherapy, and Survival After Esophagectomy With Three-Field Lymph Node Dissection for Thoracic Esophageal Squamous Cell Carcinoma - Chen, Junqiang; Pan, Jianji; Zheng, Xiongwei; Zhu, Kunshou; Li, Jiancheng; Chen, Mingqiang; Wang, Jiezhong; Liao, Zhongxing (International journal of radiation oncology, biology, physics, 2012)
To analyze influences of the number and location of positive lymph nodes and postoperative radiotherapy on survival for patients with thoracic esophageal squamous cell carcinoma (TE-SCC) treated with radical esophagectomy with three-field lymphadenectomy. A total of 945 patients underwent radical esophagectomy plus three-field lymph node dissection for node-positive TE-SCC at Fujian Provincial Tumor Hospital between January 1993 and March 2007. Five hundred ninety patients received surgery only (S group), and 355 patients received surgery, followed 3 to 4 weeks later by postoperative radiotherapy (S+R group) to a median total dose of 50 Gy in 25 fractions. We assessed potential associations among patient-, tumor-, and treatment-related factors and overall survival. Five-year overall survival rates were 32.8% for the entire group, 29.6% for the S group, and 38.0% for the S+R group ( p = 0.001 for S vs. S+R). Treatment with postoperative radiotherapy was particularly beneficial for patients with ≥3 positive nodes and for those with metastasis in the upper (supraclavicular and upper mediastinal) region or both the upper and lower (mediastinal and abdominal) regions ( p < 0.05). Postoperative radiotherapy was also associated with lower recurrence rates in the supraclavicular and upper and middle mediastinal regions ( p < 0.05). Sex, primary tumor length, number of positive nodes, pathological T category, and postoperative radiotherapy were all independent predictors of survival. Postoperative radiotherapy was associated with better survival for patients with node-positive TE-SCC, particularly those with three or more positive nodes and positive nodes in the supraclavicular and superior mediastinal regions.